Ecologically Oriented Professional Development of Teachers of Higher and Secondary Schools and Vocational Training Colleges - Alena Tsimanava; Aliaksandr Hrachanikau; Iryna Semianchukova; Ivan Tsimanov (Vestnik of Vitebsk State Technological University, 2017)
The article analyses problems which lead to the necessity of development of the new concept of the practice-oriented ecological education. It is noted that one of the factors constraining development of tutoring and education in this direction is low level of readiness of the modern teacher for exercise of education in the field of ecological environment. On the basis of the research held within the international project TEMPUS EcoBRU «Ecological Education for Belarus, Russia and Ukraine» and educational and methodical materials of distant advanced training courses for teachers of professional educational institutions are developed. The main objective of the developed courses is integration of knowledge of ecological environment and a subject of vocational training of specialists on the basis of the practice-oriented approach. The developed courses have been tested in target groups of teachers, and also in educational process of «VSTU» and received positive assessment of experts of the project. Introduction of courses promotes inclusion of an ecological component in process of vocational training of specialists, realization of the practice-oriented approach in tutoring, to formation of ecological competence of future specilaists.